Carcinoid abdominal crisis: A case report. Issue 3 (23rd May 2014) - Jacobs, Ramon E.A.; Bai, Shuting; Hindman, Nicole; Shah, Paresh C.
<x xml:space="preserve">Abstract</x> Over the past 40 years, the incidence of neuroendocrine tumors (NETs) has been increasing. Distal small bowel (i.e., midgut) NETs most often cause carcinoid syndrome manifested as cutaneous flushing, diarrhea, bronchial constriction, and cardiac involvement. Carcinoid abdominal crisis occurs when submucosal tumors impede the vascular supply to the gut leading to mesenteric ischemia and worsening abdominal pain. Here, we report the case of a young woman with progressively worsening abdominal pain. J. Surg. Oncol. 2014 110:348–351. © 2014 Wiley Periodicals, Inc.